16S Ribosomal RNA-Based Analysis of Thermophilic Bacteria in Gedongsongo Hot Spring - AGUSTINA LULUSTYANINGATI NURUL AMININ1; FIDA MADAYANTI; PINGKAN ADITIAWATI; . AKHMALOKA (Indonesian Society for microbiology, 2007)
Denaturing gradient gel electrophoresis was used to identify the bacterial community at the Gedongsongo (WGS-2) hot spring. The bacterial samples were obtained from both culture dependent and independent strategies. Partial 16S rRNA genes were amplified by a set of primers to produce at around 400 bp fragments, including the highly variable V9 region of the 16S rRNA genes. The DGGE profiles showed that there were a few distinct bands, namely G1-G3, and G8-G12, which represent the predominant bacteria in natural habitat and the medium.Further analysis of these bands showed that most of them, except for G7, have a high homology to the 16S rRNA gene sequences of Thermus sp. As for G7, the highest homology was shown to unculturable bacteria. In addition to the distinct bands in DGGE, there were other three thin bands, namely G4, G5, and G6, which possibly represent non dominant microorganisms in the natural habitat, but could grow on GS-A medium. Further analysis of these bands showed that G6 has 80% similarity to the 16S rRNA of Burkholderia sp., while G4 and G5 have a high homology to each other but only contained 10-15% homology to the sequences of 16S rRNA from unculturable microorganisms. The phylogenetic analyses of the last organisms showed that there was branching from Burkholderia. From all the data obtained it was suggested that the WGS-2 hot spring was predominantly occupied by the genus Thermus. In addition, there were a few novel microorganisms found in the hot spring.